2017
DOI: 10.1042/bcj20170354
|View full text |Cite
|
Sign up to set email alerts
|

The helicase, DDX3X, interacts with poly(A)-binding protein 1 (PABP1) and caprin-1 at the leading edge of migrating fibroblasts and is required for efficient cell spreading

Abstract: DDX3X, a helicase, can interact directly with mRNA and translation initiation factors, regulating the selective translation of mRNAs that contain a structured 5′ untranslated region. This activity modulates the expression of mRNAs controlling cell cycle progression and mRNAs regulating actin dynamics, contributing to cell adhesion and motility. Previously, we have shown that ribosomes and translation initiation factors localise to the leading edge of migrating fibroblasts in loci enriched with actively transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Another 5′UTR-mediated RNA-dependent interaction occurs between DDX3X and CAPRIN1. These RBPs exploit structured UTRs to control translation through PABPC1 and promote cell migration and spreading (Figure 2A ) (Copsey et al, 2017 ). Interactions in translational control also occur within the 3′UTR.…”
Section: Cooperative Target Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 5′UTR-mediated RNA-dependent interaction occurs between DDX3X and CAPRIN1. These RBPs exploit structured UTRs to control translation through PABPC1 and promote cell migration and spreading (Figure 2A ) (Copsey et al, 2017 ). Interactions in translational control also occur within the 3′UTR.…”
Section: Cooperative Target Regulationmentioning
confidence: 99%
“…(A) Shows the 5′UTR-mediated cooperation of DDX3X and CAPRIN1 which controls the translation of RAC1 mRNA. This RNA-dependent association exploits a further interaction with PABPC1 at the leading edge of the cell to promote fibroblasts migration and spreading (Copsey et al, 2017 ). (B) Depicts the antagonistic interaction of YBX1 and PABPC1 on the 3′UTR of YBX1 mRNA.…”
Section: Cooperative Target Regulationmentioning
confidence: 99%
“…On the other hand, besides playing a role in stress granule formation [47], G3BP1 has been also reported as a protein involved in the control of cell proliferation, promoting S-phase entry in fibroblasts [48], in the regulation of apoptosis through interaction with p53 and its translocation [49], and, more recently, in the oncogenic pathways in several human cancers, including breast, gastric, colon, and liver carcinomas [50][51][52][53]. Data on the physical interaction and colocalization of DDX3X with Caprin-1 are also already available [54,55]. DDX3 is a multifunctional protein involved not only in the assembly of RNA-protein complexes during cellular stress, suggesting a role for DDX3 in translational control, but also in other aspects of RNA metabolism (transcriptional regulation of INFβ, p21waf1/cip1, E-cadherin promoters; splicing and nuclear export), in cell-cycle progression, proliferation, and apoptosis [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of caprin-1 can lead to overall inhibition of stress granule formation in cells ( 19 ). Caprin-1 and helicase colocalize in the leading edge of migrating fibroblasts to promote cell migration and spreading ( 20 ). Several studies have reported that caprin-1 overexpression is associated with the occurrence and development of tumors, such as osteosarcoma, breast cancer and colon cancer ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%